Respuesta :

kmHart
x + y = 3
2x + 4y = 8

This is a system of equations. You can solve it using elimination. Start by multiplying the top equation by -2.
(x * -2) + (y * -2) = (3 * -2)
-2x - 2y = -6

Now add that and the bottom equation. This will cancel out x.

     -2x - 2y = -6
+    2x + 4y = 8
-----------------------
             2y = 2

Solve for y.
2y = 2
y = 2/2
y = 1

Now plug 1 in for y in the first equation.

x + y = 3
x + 1 = 3

Solve for x.

x + 1 = 3
x = 3 - 1
x = 2

So x = 2 and y = 1.